1968
DOI: 10.3109/00016486809119294
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Immersion on Perception of the Oculogravic Illusion in Normal and Labyrinthine-Defective Subjects

Abstract: SUMMARY PAGE THE PROBLEMTo determine the separate and combined influences o f otolith and nonotolith sensory inputs on perception of the oculogmvic illusion. By manipulating the visual and gravitoinertial force environments i t was possible to investigate the separate and combined contributions o f 1) field b r c e receptors i n the vestibular organs and 2) nonvestibular proprioceptors stimulated by external contact support, which influenced the visually perceived direction of extrapenonal space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

1973
1973
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 7 publications
1
15
0
2
Order By: Relevance
“…FISCHER, 1930 b;GIROTTI and BORDOGNA, 1963;GIROTTI, 1963;MILLER and GRAYBIEL, 1966;CLARK and GRAYBIEL, 1966a;GRAYBIEL et al, 1968). These experiments show that the activity of the vestibular apparatus may be substituted by other postural factors, if necessary.…”
Section: F the Significance Of Vestibular Direction Cuesmentioning
confidence: 86%
“…FISCHER, 1930 b;GIROTTI and BORDOGNA, 1963;GIROTTI, 1963;MILLER and GRAYBIEL, 1966;CLARK and GRAYBIEL, 1966a;GRAYBIEL et al, 1968). These experiments show that the activity of the vestibular apparatus may be substituted by other postural factors, if necessary.…”
Section: F the Significance Of Vestibular Direction Cuesmentioning
confidence: 86%
“…Sin embargo, la información procedente de los canales semicirculares y de otros sensores corporales de posición también participan en la aportación vestibular. Se han realizado estudios en inmersión para intentar anular las contribuciones somatosensorial y visual en la percepción de la vertical visual y postural y así maximizar la procedente del sáculo y del utrículo [4]. Aunque la información somatosensorial es más relevante para el mantenimiento de la postura vertical (percepción subjetiva de la verticalidad propia), también interviene en la estimación de la VVS, con la información visual y vestibular ya comentada.…”
Section: Fisiopatologíaunclassified
“…Para la mayoría de los autores no se considera necesaria la fijación vertical de la cabeza durante la medición de la VVS. La aportación somatosensorial cervical no es relevante cuando la información otolítica está disponible como se ha podido comprobar en estudios de la VVS en sujetos en inmersión [4], o en pacientes que sufren de tortícolis [8]. Por otra parte, si la información otolítica no estuviera disponible, la fijación cervical en posición vertical podría servir de referencia al paciente para la apreciación vertical del marcador.…”
Section: Proceso De Comparaciónunclassified
“…The otolith organs and central computational mechanisms are optimized for upright position, and an increase of trial-to-trial variability with increasing whole body roll has been observed when carrying out SVV tasks (De Vrijer et al 2008;Mittelstaedt 1983;Schoene and Udo de Haes 1968;Tarnutzer et al 2009aTarnutzer et al , 2009b. Manipulations of the environment, such as obtaining the SVV while roll-tilted under water, have shown that the influence of proprioception on the SVV is minor compared with that of otolith input in healthy human subjects (Graybiel et al 1968;Jarchow and Mast 1999;Wade 1973). For visual as well as haptic line adjustments along an Earth-vertical (gravicentric) axis or a body-longitudinal (egocentric) axis, Tarnutzer and colleagues observed roll angle-dependent modulations of alignment precision in all conditions (Tarnutzer et al 2012).…”
Section: In This Study We Investigated the Potential Impact Of Directmentioning
confidence: 99%